PENGARUH DAN EFEKTIFITAS BANTUAN PROGRAM KELUARGA HARAPAN (PKH) TERHADAP PARTISIPASI PENDIDIKAN DI KECAMATAN MUARA TIGA KABUPATEN PIDIE - Lidiana, Mohd Nur Syechalad, Muhammad Nasir. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2014)
Abstract: The purpose of this study was to determine the effect and effectiveness of the Family Assistance Program (PKH ) on Enrollment at Muara Tiga Kabupaten Pidie . The population of this study were all heads of families who receive the aid of family assistance program at Muara Tiga Kabupaten Pidie. Sampling was done by using the